1997
DOI: 10.1007/s000110050173
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmental stress on tissue survival and neutrophil recruitment in surgical skin flaps in relation to plasma corticosterone levels in the rat

Abstract: Skin flap survival in rats exposed to environmental stress may be significantly increased as compared to animals accustomed to their new environment for one week, possibly as a consequence of anti-inflammatory actions exerted by stress-induced elevations in plasma corticosterone. These findings emphasize the importance of strictly controlling environmental stress factors in studies of inflammation and tissue damage after surgical skin trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 24 publications
4
16
1
Order By: Relevance
“…Appropriate proportion depends on the vascularity and sub dermal plexus of each area, about 3 -4 to 1 length to width (10). However, in every condition, flap ischemia and necrosis may occur (8). Many drugs have been studied in preventing flap ischemia and necrosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Appropriate proportion depends on the vascularity and sub dermal plexus of each area, about 3 -4 to 1 length to width (10). However, in every condition, flap ischemia and necrosis may occur (8). Many drugs have been studied in preventing flap ischemia and necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, in these studies, flaps have a wide range of viability in control and treatment groups. Differences in race, sex, and feeding order of rats, design of flap, time of study, amount of drug, and infection after surgery can explain this variety (8) and should be considered in concluding the results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Glucocorticoids may thus directly affect the inner ear function under physiological and pathological conditions. It has been shown that concentrations of dexamethasone, which can activate glucocorticoid receptors, ranged from 100 nM to 1 µM under normal and stress conditions [106][107][108]. In the rat inner ear, the plasma concentrations of glucocorticoids were elevated up to 1 µM under noise conditions [104].…”
Section: Effects Of Glucocorticoids On the Atp-induced No And Ca 2+ Smentioning
confidence: 99%